FDG-PET/CT for Detection of Extramedullary Disease in 2 Pediatric Patients With AML. Issue 5 (July 2016) - Matsui, Motohiro; Yamanaka, Junko; Shichino, Hiroyuki; Sato, Noriko; Kubota, Kazuo; Matsushita, Takeji
Abstract : Positron emission tomography combined with computed tomography (PET/CT) is a promising diagnostic procedure for the detection of extramedullary disease (EMD) in acute myeloid leukemia. We studied 2 children with acute myeloid leukemia who underwent PET to assess for EMD at diagnosis as well as in remission. We detected 5 EMD lesions in 2 cases with PET, only 2 of which were detectable on clinical examination. Our cases show PET's increased sensitivity over physical examination alone in assessing and monitoring the extent of this disease.